2014
DOI: 10.1039/c4ee01389a
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency single-junction semitransparent perovskite solar cells

Abstract: Semitransparent efficient methylammonium lead iodide perovskite based solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
241
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(244 citation statements)
references
References 52 publications
2
241
1
Order By: Relevance
“…[ 71 ] Roldán-Carmona et al used a 6 nm thick gold electrode and a LiF capping layer to protect the gold layer and reduce refl ection, obtaining a 6.4% PCE and a 29% AVT. [ 72 ] Cheng et al improved the transparency and conductivity of the transparent electrode by using a MoO 3 -Au-MoO 3 confi guration ( Figure 6 a). [ 73 ] MoO 3 helped to form a thin and uniform Au layer, leading to enhanced conductivity.…”
Section: Semitransparent Cellsmentioning
confidence: 99%
“…[ 71 ] Roldán-Carmona et al used a 6 nm thick gold electrode and a LiF capping layer to protect the gold layer and reduce refl ection, obtaining a 6.4% PCE and a 29% AVT. [ 72 ] Cheng et al improved the transparency and conductivity of the transparent electrode by using a MoO 3 -Au-MoO 3 confi guration ( Figure 6 a). [ 73 ] MoO 3 helped to form a thin and uniform Au layer, leading to enhanced conductivity.…”
Section: Semitransparent Cellsmentioning
confidence: 99%
“…It has been proved in our previous works [28][29][30][31] and other reports [32][33][34] that the ultrathin Ag film with a suited optical coupling layer could meet the requirements of a transparent electrode. Our simulations [28] about bifacial semitransparent PSCs have shown that the maximum possible current density of a device illuminated from the Ag side rapidly increases with the decreasing Ag thickness, while it gradually decreases for the reverse illumination direction from the ITO side.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the considerable efforts devoted to pursuing high efficiencies via improved crystallization of perovskite and searching for low-cost interface materials, 4,10-13 aesthetic semitransparent perovskite solar cells have been simultaneously receiving growing attention because of their specific application in transparent architectures, [14][15][16][17] such as windows, rooftops, greenhouses and other fashion elements. To achieve efficient semitransparent perovskite devices, both the anode and the cathode of the devices should be highly transparent and conductive in order to minimize the optical and resistance losses.…”
mentioning
confidence: 99%
“…To date, several studies have reported semitransparent perovskite solar cells, but most of these devices employed thin metal films (Al, Ag, Au) as top electrodes which were fabricated based on energy-intensive evaporation processes. [15][16][17] It is well known that, in addition to low-cost materials, the cost reduction of photovoltaic devices substantially depends on the ability to use high-throughput coating techniques in combination with roll-to-roll processing. 18 Despite its importance, however, less attention has been paid to the exploration of solution-processable transparent electrodes for perovskite solar cells.…”
mentioning
confidence: 99%